ANALISIS LINGUISTIK MATERI BACAAN DALAM BUKU TEKS BAHASA INDONESIA - Niswatin, Siti Innayati (WAHANA PEDAGOGIKA, 2016)
The purpose of this research is to find materials words and phrases in text books Indonesian. This study is a descriptive-qualitif. The analysis techniques of data is used include data reduction, data presentation, and conclusion. The results showed that in terms of the type and form of the word there are types of verbs, nouns, adjectives, and numeralia. The forms of verb consist of basic verbs, verbs affixed ber-an and verb affixed me-kan. Forms of nouns consisting of basic nouns, nouns affixed ke-an, nouns affixed pe-an, and noun affixed per-an. Forms of adjectives consists of basic adjective, adjective affixed me-kan, adjective affixed ter-. Material phrases found in the text book reading material that is used as a data source consists of (1) the nominal phrase, (2) verb phrase, (3) an adjective phrase, (4) prepositional phrases, and (5) phrases adverbal.